Development of lacrimal gland organoids from iPSC derived multizonal ocular cells - Asal, Melis; Koçak, Gamze; Sarı, Vedat; Reçber, Tuba; Nemutlu, Emirhan; Utine, Canan Aslı; Güven, Sinan (Frontiers in Cell and Developmental Biology, 2023)
Lacrimal gland plays a vital role in maintaining the health and function of the ocular surface. Dysfunction of the gland leads to disruption of ocular surface homeostasis and can lead to severe outcomes. Approaches evolving through regenerative medicine have recently gained importance to restore the function of the gland. Using human induced pluripotent stem cells (iPSCs), we generated functional in vitro lacrimal gland organoids by adopting the multi zonal ocular differentiation approach. We differentiated human iPSCs and confirmed commitment to neuro ectodermal lineage. Then we identified emergence of mesenchymal and epithelial lacrimal gland progenitor cells by the third week of differentiation. Differentiated progenitors underwent branching morphogenesis in the following weeks, typical of lacrimal gland development. We were able to confirm the presence of lacrimal gland specific acinar, ductal, and myoepithelial cells and structures during weeks 4-7. Further on, we demonstrated the role of miR-205 in regulation of the lacrimal gland organoid development by monitoring miR-205 and FGF10 mRNA levels throughout the differentiation process. In addition, we assessed the functionality of the organoids using the β-Hexosaminidase assay, confirming the secretory function of lacrimal organoids. Finally, metabolomics analysis revealed a shift from amino acid metabolism to lipid metabolism in differentiated organoids. These functional, tear proteins secreting human lacrimal gland organoids harbor a great potential for the improvement of existing treatment options of lacrimal gland dysfunction and can serve as a platform to study human lacrimal gland development and morphogenesis.